Phylogeography And Genetic Variation Of The Bighead Catfish, Clarias macrocephalus (Günther, 1864) From Peninsular Malaysia And Mekong River Basin Based On Mitochondrial And Microsatellite Markers - Abdul Kadar, Nazia (2014)

(untitled)
Mitochondrial and microsatellite markers were utilised to investigate the genetic diversity and phylogenetic relationships among catfish, Clarias macrocephalus populations from Peninsular Malaysia and two Mekong River Basin regions, namely Cambodia and Vietnam. For mitochondrial analyses, 332 individuals from 19 populations were sequenced for Cytochrome b (609 bp) gene while 382 individuals from 19 populations were analysed for the D-loop (479 bp) gene. Penanda mitokondria dan mikrosatelit telah digunakan untuk mengkaji variasi genetik dan hubungan filogenetik di kalangan populasi ikan keli, Clarias macrocephalus dari Semenanjung Malaysia dan dua rantau lembangan sungai Mekong iaitu Kemboja dan Vietnam. Untuk analisis mitokondria, 332 individu dari 19 populasi telah dibuat penjujukan untuk gen Cyt b (609 bp) manakala 382 individu dari 19 populasi untuk gen D-loop (479 bp).